PERANCANGAN ANIMASI MULTIMEDIA IKLAN LAYANAN MASYARAKAT TENTANG PROSES PEMBUATAN E-KTP - Rudianto, Rudianto; Budi Bayu, Budi Bayu; Aulia, Rahmi; Fadilah, Fadilah (Aksara Public, 2018)
E-KTP (KTP-el) is a state document that must be owned by every citizen who has been aged 17 years or has married or been married. every citizen has only 1 E-KTP card in which there is a Population Identity Number (NIK). NIK became the sole identity number for public service affairs (Law Number 24 of 2013 About Amendment To Law Number 23 of 2006 About Population Administration). However, the implementation of E-KTP is still not maximized, one of the problems is the lack of socialization and information on E-KTP to citizens. As the result of a poll conducted by e-ktp.com up to the beginning of 2016, it was found that 58.0% of people complained about the lack of socialization and information on E-KTP, and only 3.0% -9.0% expressed satisfaction with the socialization and information which exists. In fact, until the middle of 2016 there are about 22 million inhabitants scattered in various areas that have not done recording E-KTP. Therefore the authors try to make multimedia animation in the form of public service ads to provide education and explain how the process of making and the E-KTP for the community. The design of multimedia animation using Luther-Sutopo version of multimedia development method with 6 stages is concept, design, collecting material, assembly, testing and distribution.